2008
DOI: 10.1111/j.1551-2916.2008.02671.x
|View full text |Cite
|
Sign up to set email alerts
|

Dense YMn2O5 Ceramics Prepared by Spark Plasma Sintering

Abstract: Dense multiferroic YMn2O5 ceramics with a single orthorhombic phase are quite difficult to prepare because the orthorhombic phase decomposes at about 1180°C. In this study, spark plasma sintering (SPS) was investigated to synthesize YMn2O5 ceramics. The sample sintered at 900°C for 5 min by SPS consisted of the main orthorhombic YMn2O5 phase and a small amount of hexagonal YMnO3 phase and Mn3O4. After heat treatment at 1100°C for 9 h, YMn2O5 ceramics in a single orthorhombic phase with a relative density of 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Accordingly, this transformation can occur in the 1050 °C-sintered sample. This behavior is in accordance with the finding reported in [27]. In summary, the unique YFeO 3 phase without impurities can only be acquired for the 1000 °C-sintered sample, which is 300–400 °C lower compared to conventional methods.…”
Section: Resultssupporting
confidence: 92%
“…Accordingly, this transformation can occur in the 1050 °C-sintered sample. This behavior is in accordance with the finding reported in [27]. In summary, the unique YFeO 3 phase without impurities can only be acquired for the 1000 °C-sintered sample, which is 300–400 °C lower compared to conventional methods.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, the spark plasma sintering (SPS) method has been used widely as a low temperature and rapid sintering method in the past decade [19][20][21][22][23][24][25]. The dense ceramics with smaller grain size, for example, nano-scale, can be easily prepared by SPS method because of its much lower sintering temperature and time [25].…”
Section: Introductionmentioning
confidence: 99%
“…Three compounds, YMnO 3 , YMn 2 O 5 , and Y 2 Mn 2 O 7 , have been reported in the system . YMnO 3 has three modifications: two hexagonal phases ( h F / h p ‐YMnO 3 ) and an orthorhombic phase ( o ‐YMnO 3 ) .…”
Section: Literature Survey On the Bao–y2o3–mno2 Systemmentioning
confidence: 99%
“…Compound YMn 2 O 5 has an orthorhombic structure in S.G. Pbam with a = 7.2639 (2), b = 8.4758 (2) and c = 5.6673 (1) Å at room temperature . Gao et al . reported that the YMn 2 O 5 compound was easily synthesized at 1100°C, but decomposed into YMnO 3 and Mn 3 O 4 at 1200°C.…”
Section: Literature Survey On the Bao–y2o3–mno2 Systemmentioning
confidence: 99%